Vibration characteristics of novel multilayer sandwich beams: Modelling, analysis and experimental validations. (August 2020) - Li, Meng; Du, Shaojun; Li, Fengming; Jing, Xingjian
Highlights: Dynamic modellings of the novel multilayer lattice sandwich beams are developed. Novel deformation relations of multilayer sandwich beams are established. Vibration properties of multilayer sandwich beams are systematically studied. Vibration experiments are carried out to validate the proposed modellings. Effects of truss core direction, truss core radius and sheet thickness are analyzed. Abstract: Multilayer sandwich structures have been extensively studied. However, very few results are reported on the vibration issues of some novel multilayer sandwich structures with lattice truss cores in the literature. To this aim, in this paper, the dynamic modellings of multilayer sandwich beams with pyramidal lattice truss cores are developed, and the vibration characteristics of multilayer lattice sandwich beams are numerically investigated and validated by vibration experiments. The deformation relations of multilayer sandwich beams are theoretically developed in this study, and consequently the constitutive relations of the truss core layers of multilayer sandwich beams are derived by using such a deformation energy based method. Hamilton's principle and the assumed mode method are used to derive the equations of motion of the multilayer sandwich beams. The natural frequencies of the multilayer lattice sandwich beams are obtained and compared with those from the finite element method (FEM) and experimental tests, which all verified the correctness and feasibility of the proposed numerical method. Contributions of this study lie in the development of the novel deformation relations of multilayer sandwich beams, establishment of the dynamic models, and systematic analysis of vibration characteristics with both the numerical and experimental methods. The present work would facilitate the application of multilayer truss core sandwich structures in engineering fields.